Frontispiece: From Bola‐Surfactant Templated Bimetal Phosphites to the Design of Crystalline Inorganic Mesoporous Frameworks. Issue 21 (12th April 2017) - Huang, Hui‐Lin; Huang, Wen‐Yen; Wang, Sue‐Lein
Abstract : Reproducing inorganic modules for pore augmentation of pure inorganic frameworks is challenging but can be a key to rational synthesis. In their Communication onpage 4962 ff., S.‐L. Wang and colleagues describe how the use of bola‐type surfactant not only successfully reproduces inorganic building modules that were previously observed in the NTHU‐13 system, but also provides two additional modules to allow the design of two new series with channel‐sizes spanning the micro‐ and mesoporous regimes.